2018
DOI: 10.1002/aelm.201800091
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Annealing Ferroelectric HfO2 Thin Films: In Situ, High Temperature X‐Ray Diffraction

Abstract: crystalline phase in doped HfO 2 thin film. [17,18] However, this phase cannot be observed in the phase diagram of bulk HfO 2 and ZrO 2 , [19,20] even when doped with elements that are used in the thin film counterparts. [21] Therefore, multiple factors were suggested as origin of the stabilization of the ferroelectric phase. Materlik et al. suggested that the o-phase can be stabilized due to surface energy effects, [22] and Park et al. comprehensively examined the surface energy model and their experimental o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(64 citation statements)
references
References 63 publications
4
60
0
Order By: Relevance
“…They concluded that surface energy contributions were negligible and the FE phase is stabilized by the impact of the dopant, which is supported by the high‐temperature XRD. Instead of a transformation toward a monoclinic phase at highest temperatures as in earlier studies, a tetragonal phase forms, which then transforms to an orthorhombic phase during cool down.…”
supporting
confidence: 50%
“…They concluded that surface energy contributions were negligible and the FE phase is stabilized by the impact of the dopant, which is supported by the high‐temperature XRD. Instead of a transformation toward a monoclinic phase at highest temperatures as in earlier studies, a tetragonal phase forms, which then transforms to an orthorhombic phase during cool down.…”
supporting
confidence: 50%
“…The linear coefficient of thermal expansion of the LSMO layer can be estimated as 11.94(60.05) Â 10 À6 K À1 . We note from the work of Park et al 12 that TiN, a commonly used electrode in doped-hafnia devices, starts to degrade via intermixing and formation of rutile TiO 2 between 800 and 950 C. Contrastingly, our LSMO electrodes (complex oxide electrodes) are very stable under these conditions at least until 850 C.…”
mentioning
confidence: 70%
“…In polycrystalline TiN/doped-hafnia samples, there is no clear structural signature of a reversible ferroelectric to paraelectric phase transition obtained from comprehensive in situ high temperature x-ray diffraction (XRD) studies. 12 Third, domain wall motion and domain wallassisted transitions 13 have not been reported in these systems. 14,15 Recently, there has been a theoretical breakthrough, which suggested that, indeed, ferroelectricity in o-phase hafnia is of a different type, associated with flat phonon bands and 2D polar planes in a nonpolar matrix.…”
mentioning
confidence: 94%
“…In this work, we analyze a metal‐insulator‐metal stack fabricated as outlined earlier with 20 nm thick La:HfO 2 with 10 cat% La. How exactly the dominant orthorhombic phase is formed during the anneal cannot be directly observed, but previous temperature dependent XRD measurements typically indicate a crystallization of similar amorphously deposited films starting at temperatures around 500 °C. The results can provide insight into the presence of strain as a consequence of residual stress in the film.…”
Section: Spontaneous Polarization Stress and Strainmentioning
confidence: 99%